Risk Factors Associated with Acute Respiratory Distress Syndrome in Pediatrics - Awan, Dilawar Abbas; Sharif, Zubair; Naeem, Usra; Batool, Taseer; Habib, Ghalib; Shahzadi, Kiran (Indus Journal of Bioscience Research, 2025)
Background: Every expectant mother hopes for a healthy baby, yet complications during delivery can lead to severe conditions like acute respiratory distress syndrome (ARDS). This study aims to identify key risk factors associated with ARDS in pediatric patients. Methodology: A questionnaire was developed through a literature review to identify key ARDS risk factors in pediatrics. The questionnaire was verified by a panel of pediatric experts, and its reliability was tested (Cronbach’s alpha = 0.5). Results: Among the infants, 55% were male and 45% female. APGAR scores showed 36% had mild depression, 46% moderate, and 18% severe asphyxia. Mechanical ventilation was required for 40% of patients. Preterm births accounted for 67.13% of cases, while 64.3% were term and 8.4% late-term. C-section deliveries were common (65.03%), and 41% of patients had raised bilirubin levels. Only 20% were breastfed, while 58% required nasogastric tubes. Most patients (81.82%) were aged 1 day to 1 month. Hospital stays varied: 35% in days, 46% in weeks, and 19% in months. Advanced Cardiac Life Support was needed for 29%, and blood transfusions for 24%. Ventilator modes varied, with nasal cannula (45%) being the most used. PaO₂/FiO₂ ratios were normal in 29%, mild in 33%, moderate in 21%, and severe in 17%. Mortality was 24%. Conclusion: Preterm birth and mechanical ventilation were the major risk factors for pediatric ARDS. Sepsis, HIE II & III, pneumonia, metabolic disorders, and meconium aspiration were prevalent diagnoses.Surfactant therapy was associated with a 68% mortality rate, emphasizing its impact on lung maturity.